2016
DOI: 10.1038/srep26171
|View full text |Cite
|
Sign up to set email alerts
|

The proactive bilingual brain: Using interlocutor identity to generate predictions for language processing

Abstract: The present study investigated the proactive nature of the human brain in language perception. Specifically, we examined whether early proficient bilinguals can use interlocutor identity as a cue for language prediction, using an event-related potentials (ERP) paradigm. Participants were first familiarized, through video segments, with six novel interlocutors who were either monolingual or bilingual. Then, the participants completed an audio-visual lexical decision task in which all the interlocutors uttered w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 35 publications
3
39
0
Order By: Relevance
“…Indeed, this region was not sensitive to the CTI manipulation, suggesting a similar involvement for reactive and proactive control. It is possible that, when conditions allow doing so, language control relies particularly on proactive processes (Martin et al, 2016;Molnar et al, 2015). In language switching this strategy may be crucial to adjust performance according to continuously changing goals.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, this region was not sensitive to the CTI manipulation, suggesting a similar involvement for reactive and proactive control. It is possible that, when conditions allow doing so, language control relies particularly on proactive processes (Martin et al, 2016;Molnar et al, 2015). In language switching this strategy may be crucial to adjust performance according to continuously changing goals.…”
Section: Discussionmentioning
confidence: 99%
“…Results obtained with the cued language-switching paradigm should be particularly relevant in explaining the mechanisms involved in such naturally occurring situations. Research has shown that bilinguals may benefit from using the language associated with an interlocutor or their apparent cultural identity as a cue to use one language and not another (Blanco-Elorrieta & Pylkkänen, 2015;Hartsuiker, 2015;Li, Yang, Scherf, & Li, 2013;Liu, Timmer, Jiao, Yuan, & Wang, 2019;Martin, Molnar, & Carreiras, 2016;Woumans et al, 2015). At the neurophysiological level, interlocutor identity has indeed been found to be represented in a sustained fashion during the planning stages that precede speech onset (Blanco-Elorrieta & Pylkkänen, 2017).…”
Section: Ecological Validity Of Research Findings On Bilingual Languamentioning
confidence: 99%
“…Rather, familiarity with a speaker is enough to create an association between a language and a face that results in faster naming than when this association is absent [41]. Related recent research on bilingual language processing with different paradigms and tasks has additionally suggested that using naturalistic cues facilitates predictions about upcoming language [42,43] (for a review on the role of visual cues for language selection see [44]).…”
Section: Switching In Response To Natural Cuesmentioning
confidence: 99%